A Human-Derived Monoclonal Antibody Targeting Extracellular Connexin Domain Selectively Modulates Hemichannel Function - Ziraldo, Gaia; Buratto, Damiano; Kuang, Yuanyuan; Xu, Liang; Carrer, Andrea; Nardin, Chiara; Chiani, Francesco; Salvatore, Anna Maria; Paludetti, Gaetano; Lerner, Richard A.; Yang, Guang; Zonta, Francesco; et al. (Frontiers in Physiology, 2019)
"The full text of this article will be available once it has been published."